6,6′-Dimethoxy-2,2′-[p-phenylenebis(nitrilomethylidyne)]diphenol chloroform disolvate - Al-Douh, Mohammed Hadi; Osman, Hasnah; Abd Hamid, Shafida; Kia, Reza; Fun, Hoong-Kun (International Union of Crystallography, 2009)
The title compound, C22H20N2O4·2CHCl3, a new Schiff base compound, lies across a crystallographic inversion centre. An intramolecular O-HN hydrogen bond generates a six-membered ring, producing an S(6) ring motif. Intermolecular bifurcated C-HO hydrogen bonds involving the two O atoms of the Schiff base ligand and the H atom of the chloroform solvent of crystallization, generate an R21(5) ring motif. The crystal structure is stabilized by intermolecular C-H and - interactions [centroid to centroid distance = 3.6158 (10) Å]. In the crystal structure, molecules are stacked down the c axis.